RFID-based Positioning System in Complex Environments - Mudrik Alaydrus (Journal of ICT Research and Applications, 2011)
For effective identification of objects, Radio Frequency Identification (RFID) is  used in miscellaneous activities. In recent times, RFID is also used for positioning purposes. We show a scenario of wireless propagation  in free space observed by  up to  eight antennas with different polarization located in different positions. In this way, the polarization and diagram radiation of the antennas will play  a  significant role  in  producing  electromagnetic  field  in  the  region.   In  the second  case,  the  effects  of  disturbances  in  form  of  metallic  boxes  are  studied. The determination of the position is carried out by fingerprinting procedure.